2021
DOI: 10.5152/tud.2020.20201
|View full text |Cite
|
Sign up to set email alerts
|

Renal tumor growth rate in patients with previously normal CT scan: Analysis of the initial stage of growth

Abstract: Ali Serdar Gözen, et al.; Robot-assisted vasovasostomy and vasoepididymostomy: Current status and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…No correlation was shown between tumor linear growth rate and the Fuhrman grading system, gender, histology, or age. 13 In our patient, the tumor grew approximately 0.89 cm per year after diagnosis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…No correlation was shown between tumor linear growth rate and the Fuhrman grading system, gender, histology, or age. 13 In our patient, the tumor grew approximately 0.89 cm per year after diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…Studies conducted by Ameri et al 13 revealed differences in the linear tumor growth rates before and after six months. No correlation was shown between tumor linear growth rate and the Fuhrman grading system, gender, histology, or age.…”
Section: Discussionmentioning
confidence: 96%
“…The growth rate of tumors may be influenced by multiple factors including tumor size, number and type of genetic mutations, blood supply, and host immune status. Studies conducted by Ameri et al (13) revealed differences in the linear tumor growth rates before and after six months. No correlation was shown between tumor linear growth rate and the Fuhrman grading system, gender, histology, or age (13).…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted by Ameri et al (13) revealed differences in the linear tumor growth rates before and after six months. No correlation was shown between tumor linear growth rate and the Fuhrman grading system, gender, histology, or age (13). The study conducted by Finelli et al (14) showed that the growth rate of renal cell carcinoma subtypes varies, and the growth rate of clear cell RCC was faster than that of papillary type 1, which may reflected the individual host and tumor biology.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation